Murder of a president [videorecording (DVD)] : romance, madness, medicine, and the death of James A. Garfield - Rapley, Rob; Murphy, Michael, 1938-; Miller, Candice (PBS Distribution, 2016)
Recounts the assassination and excruciating final months of President James Garfield's life. A brilliant scholar, courageous general, and fervent abolitionist, Garfield never wanted the job of president. But once in office, he worked tirelessly to reunite a nation still divided 15 years after the Civil War. As he lay dying, the North and South came together to pray for his recovery.